Movement related desynchronisation pattern preceding voluntary movement in untreated Parkinson's disease. Issue 3 (March 1996) - Defebvre, L; Bourriez, J L; Destée, A; Guieu, J D
Abstract : OBJECTIVE--To study planning of movement in Parkinson's disease. METHODS--The spatiotemporal pattern of movement related desynchronisation (MRD) preceding a self paced voluntary wrist flexion was compared between two groups of 10 untreated right and left hemiparkinsonian patients receiving no treatment and 10 control subjects. The MRD was computed in the 9 to 11 Hz frequency band from 11 source derivations covering the frontocentral, central, and parietocentral areas, during two successive left and right experimental conditions. RESULTS--In the two patient groups the desynchronisation appeared over the primary sensorimotor area contralateral to the affected side with a shorter latency (750 ms before movement onset for the right hemiparkinsonian group and 875 ms for the left hemiparkinsonian group) than in the control group (1750 ms), only when the movements were performed with the akinetic hand. For the non-affected hand, the same latency as in the control group was noted (1750 ms). CONCLUSION--The delay of appearance of MRD in Parkinson's disease confirmed that the programming of movement is affected, thus partially explaining akinesia.